Thermoelastic slutions for flexure of anisotropic cylindrical shells - Mohamed Ali, Jaafar Syed (Trans Tech Publications, Switzerland, 2015)
Solutions within the framework of linear uncoupled thermoelasticity, are presented here for simply supported infinitely long anisotropic cylindrical shell panels subjected to thermal gradient. Benchmark numerical results in the form of displacements and stresses are tabulated for certain angle-ply layup useful for the assessment of improved shell theories.